Quality policy in the veterinary diagnostic laboratory; the paradigm of application of Good Laboratory Practice - ATHANASIOU (Λ.Β. ΑΘΑΝΑΣΙΟΥ) L. V. (Journal of the Hellenic Veterinary Medical Society, 2017)
A quality system such as the Good Laboratory Practice (GLP) in a veterinary diagnostic laboratory is concerned with the organizational Nprocess and the conditions under which laboratory work is planned, performed, monitored, recorded, archived and reported. The key persons for applying a quality system are the Management (provides resources), the Director (overall responsibility for the technical conduct of analyses Nand for the interpretation, analysis and reporting of results) and the Quality Assurance Person (inspects operational phases and audits documents for the purpose of assuring management that the facilities, equipment, personnel, methods, practices, records and controls are in conformance not only with applicable rules and regulations but also with Standard Operating Procedures and Laboratory Protocols). Furthermore, the Standard Operating Procedures (SOPs) that govern all aspects of daily activities at the laboratory are an essential foundation for the production of reliable data as they, by definition, describe how to perform certain routine laboratory tests or activities. The standardization of methods used for a series of critical phases, such as storage and processing of samples is required in order to eliminate systematic errors and to improve the precision, specificity and long-range stability of laboratory performance. The correct identification of all samples needs to be systematically checked. For the validation of methods used, particularly in the absence of chemical standards it is helpful to employ inter- and mainly intra laboratory controls. Finally, the disposal of chemical substances and thesafety of the personnel are also of vital interest. All these principles are applicable to a veterinary diagnostic laboratory in order to promote the quality and validity of the data with ultimate goal the contribution to a reliable diagnosis.